Limited predictability of the future thermohaline circulation close to an instability threshold - Knutti, Reto; Stocker, Thomas F. (American Meteorological Society, 2002)
Most ocean–atmosphere models predict a reduction of the thermohaline circulation for a warmer climate in the near future. Although a reduction in the Atlantic Ocean circulation appears to be a robust result, the question remains open whether the climate system could possibly cross a critical threshold leading to a complete shutdown of the North Atlantic deep-water formation. Ensemble simulations with an ocean–atmosphere climate model of reduced complexity are performed to investigate the range of possible future climate evolutions when the climate system is close to such a threshold. It is found that the sensitivity of the ocean circulation to perturbations increases rapidly when approaching the bifurcation point, thereby severely limiting the predictability of future climate. At the bifurcation point, different response types such as linear responses, nonlinear transitions, or resonance behavior are observed. Close to the threshold, thermohaline shutdowns can occur thousands of years after the warming has stopped. A characterization of the probability for the different response types reveals a more complex picture for the future evolution of the ocean circulation than previously assumed. These results raise fundamental questions of how far the large differences in projections of the Atlantic circulation response to global warming are caused by different representations of processes, parameterizations, and/or resolution in individual models and whether the predictability of the Atlantic circulation becomes inherently limited when approaching a bifurcation point.